2013
DOI: 10.1021/ed4000487
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of a Thermochromic Spin Crossover FeII Complex: An Undergraduate Coordination Chemistry Laboratory Experiment

Abstract: In this third-year undergraduate experiment, a coordination complex [Fe(NH 2 trz) 3 ]Br 2 •H 2 O (NH 2 trz is 4-amino-1,2,4-triazole, C 2 H 4 N 4 ) was synthesized and characterized by IR and UV−visible spectroscopies. This compound exhibits a spectacular reversible purple-white thermochromic transition upon heating−cooling with a large hysteresis centered at room temperature. The thermochromic transition is related to the spin crossover (SCO) from the low-spin state (LS, purple, S = 0, diamagnetic) to the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Afterward, ε of the absorption maximum is plotted as a function of the temperature. Both complexes reveal fully reversible changes in their absorption which belong to a MLCT transition during cooling and heating . Because Fe­(II) low spin compounds are generally expected to have greater extinction intensities, this reversible color change indicates a gradual SCO in solution.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Afterward, ε of the absorption maximum is plotted as a function of the temperature. Both complexes reveal fully reversible changes in their absorption which belong to a MLCT transition during cooling and heating . Because Fe­(II) low spin compounds are generally expected to have greater extinction intensities, this reversible color change indicates a gradual SCO in solution.…”
Section: Resultsmentioning
confidence: 97%
“…Both complexes reveal fully reversible changes in their absorption which belong to a MLCT transition during cooling and heating. 73 Because Fe(II) low spin compounds are generally expected to have greater extinction intensities, 73 this reversible color change indicates a gradual SCO in solution. The spin transition is detected from a high spin state at room temperature to a low spin state at lower temperature.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Figure shows the temperature dependent UV/Vis spectrum of 2 OTf in EtCN in the range from 193 to 295 K. Pronounced absorption changes are evident, with a prominent rise of a band at λ max = 417 nm upon cooling; spectral changes are fully reversible upon warming to room temperature. It is generally observed that iron(II) complexes exhibit higher extinction coefficients in their low‐spin state than in their corresponding high‐spin analogues,, suggesting that a gradual high‐spin to low‐spin transition occurs for 2 OTf in EtCN, which however is still incomplete in the accessible temperature range.…”
Section: Resultsmentioning
confidence: 99%
“…It is apparent from Eq. (18) that V 2 has the expression of exchange-like energy, so an effective exchange parameter J i,i + 1 can be defined as follows: (20) The sign of exchange constant depends on the relation between μ and (ν + λ)/2, and the exchange term disappears when the elastic constant for HS-LS case is the average of the elastic constants for LS-LS and HS-HS states, i.e., μ = (ν + λ)/2.…”
Section: Atom-phonon Coupling Modelmentioning
confidence: 99%
“…In the solid state, the structural changes associated to the spin transition propagate in a cooperative manner, which can lead to a hysteretic behavior. From an applicative point of view, SCO materials have been proposed for various technological applications such as recording media, sensors (thermal, pressure, or gas) [17][18][19][20][21], displays [4], molecular switches [22,23], memristor devices [24][25][26][27][28], or actuators [29,30].…”
Section: Introductionmentioning
confidence: 99%